Simultaneous micro measurement of steroid receptors in breast cancer. - Milano, G. (Nature Publishing Group, 1983)
The oestradiol (RE) and progesterone (RP) receptor levels were analyzed in 26 tumour fragments (200-500 mg) from breast cancer patients. After pulverization of tissue, one part was analyzed by the routine dextran-coated charcoal (DCC) method and the other by a micromethod as follows: (i) cytosol incubation using the DCC method but in the simultaneous presence of [3H]oestradiol and [3H]R5020 (ii) extraction of the steroids bound to the receptor by precipitation with ethanol/TCA (iii) high pressure liquid chromatography (HPLC) on a modular system, with a C185 microns column and an elution by gradient mixture methanol/water. The fractions were collected and the radioactivity counted. The separation of oestradiol from R 5020 was rapid and complete. In addition dexamethasone was separated by this system making possible triple measures of RE, RP and glucocorticoid receptors. A highly significant correlation was obtained between the 2 methods: RE = 0.996, P less than 0.001; RP r = 0.975, P less than 0.001, implying that the thresholds of positivity, i.e. for therapeutic decisions, remain unchanged. Simultaneous measurement of RE and RP in a single needle biopsy is possible with this micromethod.